Effect of the magnetic field and electron/hole doping on electronic heat capacity and Pauli spin susceptibility of monolayer MoS2 in the presence of electron-phonon coupling. (March 2021) - Abdi, Mona; Astinchap, Bandar
Highlights: Theoretical study of monolayer MoS2 using Holstein model Hamiltonian. Calculate magnetic susceptibility and electronic heat capacity of monolayer MoS2 in the presence of magnetic field. Curie temperature shifts to low temperature with electron injection. Revealing ferromagnetic phase with applying external magnetic field. The peak of electronic heat capacity is strongly depended on electron and hole injection. Abstract: We investigate the total electronic heat capacity (EHC) and Pauli spin susceptibility (PSS) of monolayer MoS2 in the presence of an external magnetic field and electron/hole doping by using the Holstein model. The total PSS and EHC of monolayer MoS2 were studied within the Green function method. It is found that applying an external magnetic field in the presence of the electron-phonon coupling reduces the energy band gap and Van Hove singularity split into two peaks. The total EHC is dependent on an external magnetic field and it changes differently at low and high temperatures. The electron doping reduces the total PSS and EHC, but hole doping increases both of them. Interestingly, the total PSS shows the ferromagnetic phase in the presence of an external magnetic field, and the Curie temperature shifts to low temperature with electron doping. The MoS2 phase tends to change from antiferromagnetic to ferromagnetic by holedoping. Finally, we calculated the total PSS and EHC of monolayer MoS2 as a function of an external magnetic field, electron, and hole doping with considering the electron-phonon coupling.